Replacement heifers - breeding management - Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
Records are the backbone of any breeding program. Artificial insemination (AI) is essential to maximizing genetic gain and minimizing calving problems and breeding costs. In addition, AI allows controlled calving - calving at the dairyman's discretion - not Mother Nature's! Adequately grown heifers should be added to the breeding list during the 13th month of age and serviced to meet the herd's calving goal. Feeding and handling systems should not change during the month preceding and during the breeding period, in order to minimize stress on the reproductive system. Economic loss because of delayed calving beyond 24 months of age is about $30 per month. With an average age of first calving in Kansas DHI herds of 29 months, the annual loss to Kansas dairy producers exceeds $2 million annually.
Keywords: Dairy; Replacement heifers; Breeding management; Genetics